Água da chuva: aproveitamento para a gestão de recursos pluviais em comunidades ribeirinhas do estado do Amazonas - Barboza Júnior, Paulo Cabral (2018)
Although the Amazonian territory has an expressive freshwater reserve, the large demographic dispersion of the small interior communities makes it difficult to implement the usual technological solutions for the water supply service, since this dispersion make it impossible to install a public system for their supply. Most of the local population uses the river as their first source of water to supply their needs. However, due to the lack of basic sanitation and difficult access to drinking water, the capture and use of rainwater is a common practice of the citizens who lives on the edge of the rivers and lakes of the Amazon. In 2006 the Government of Amazonas initiated a proposal for the use of pluviometric resources in its territory, with the installation of 80 rainwater harvesting systems in lowland ecosystems, in the inland areas or floating dwellings located in the municipality of Manacapuru in the RDS Piranha, and was expanded between 2007/2009 with the PROCHUVA program and, after 2014, the ÁGUA PARA TODOS program, which consisted in the implementation of home and community-based systems in villages located in the interior of the State. Currently the experience is already present in 42% of the municipalities of Amazonas. The objective of this work was to analyze the proposals for the use of this natural good in rural settlements affected by river regimes, from the installation of rainwater harvesting systems as an alternative to the management of water resources, and sought to identify if such proposals were configured as an appropriate technology alternative that would guarantee water security in the water supply of these sites. The data was provided by the State Department of the Environment of Amazonas, responsible for the implementation of the PROCHUVA and ÁGUA PARA TODOS programs in Amazonas, which served approximately 60 thousand people from 27 municipalities located in Purus, Solimões, Amazonas, Negro and Madeira rivers. The results showed that in the homes served by government programs, over 91% of them did not use filters in the processes of purification of the collected water, utilizing sodium hypochlorite and the execution of processes of coercion using a cloth the prevailing types of treatment, and that rainwater was generally reserved for the nobler purposes of drinking and cooking, The analyzes allow us to infer about the viability of installing the systems as an individual solution aimed at guaranteeing access to water suitable for human use. It is appropriate to consider some recommendations aimed at improving similar proposals that may be implemented. We can highlight changes in the design of the systems used, the use of construction techniques that take into account local characteristics, the continuity of water quality monitoring, as well as the treatment of captured water. It is also important to highlight the intensification of the processes of community mobilization, with the application of social technologies and sustainable practices aimed at the appropriation of the proposal by the beneficiaries.